Malaysian based manufacturing firms’ strategic sourcing: Self-produce or outsourcing - Abdullah, Haim Hilman; Warokka, Ari (2011)
The saga of strategic sourcing, due to the fact that globalization is inevitable and today’s manufacturers are competing in highly competitive environment, has pooled many business practices into two competing school of thoughts related to sourcing strategies, i.e. Transaction Cost Economics (TCE) Theory and Resource Based View (RBV). This paper investigated sourcing strategies and sourcing supplying countries of firms in Malaysia in responding to the intensified competition and put these strategies as an integral parts of firms’ distinctive competencies. Specifically, the results indicated sourcing strategies have significant effects to both financial and non-financial performance.However, both models indicated the ‘self-produce’ and ‘outsourcing’ strategies affect non-financial performance more than financial performance. The results also indicated the most popular supplying countries for both sourcing strategies (self-produce and outsourcing) are Malaysia, China and Singapore and majority of them received supply from one country.These findings provide new insights of sourcing practices among Malaysia based manufacturing firms and how those companies perceive and react to the competition environment surrounding them.